Morphometric parameters and photosynthetic performance of in vitro propagated pineapple - Marchi, Marcelo S. (2022)
Pineapple (Ananas comosus) is a horticultural species of the Bromeliaceae family of high socioeconomic interest, widely cultivated around the world. The multiplication of pineapple seedlings in the field can be time-consuming, requiring a significant labor investment. The objective of this study was to evaluate the performance of continuous and temporary immersion systems in the micropropagation scale-up of the species. Shoots were obtained from explants subcultured in flasks with gelled culture medium and without gas exchange. The shoots were transferred to liquid MS medium supplemented with 2mM NAA, and 4mM BAP, and cultivated in four different devices: sealed flasks, flasks with semipermeable gas membranes, RITA®, and twin-flasks. After 45 days of cultivation, plant growth, fresh mass increment, the stomatal density of the abaxial surface of the leaves, the maximum quantum yield of the photosystem II, and contents of chlorophyll and carotenoids were analyzed. Significant differences were observed in plant growth, stomatal density, and contents of chlorophyll and carotenoids. The twin-flasks and RITA® devices revealed better results in morphological parameters, such as plant growth and stomatal density, while the treatments in sealed flasks and with membrane stood out in the chlorophyll content.